2018
DOI: 10.5539/ibr.v11n11p8
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships among Emotional Demand, Job Demand, Emotional Exhaustion and Turnover Intention

Abstract: The objectives of this paper are to assess the levels of job demand, emotional demand, emotional exhaustion and employee turnover intention and to examine the relationships among these concepts in the context of three selected apparel manufacturing firms in Eastern region of Sri Lanka. Employee absenteeism and turnover are key issues of apparel firms in Sri Lanka. In order to achieve the objectives of this paper, a questionnaire based survey was conducted among 153 employees of apparel firms and collected data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 31 publications
2
19
0
9
Order By: Relevance
“…In this sense, the correlation between the ERIQ effort scale and the DECORE-21 Cognitive Demands scale indicates that they both measure similar factors. Likewise, the effort factor is closely related to the emotional exhaustion dimension of MBI-HSS, and this makes sense, since excessive demands have a positive association with exhaustion [39]. The present study has also found a high and significant positive correlation between the ERIQ Effort scale and both the Anxiety and Insomnia scales and the total score of the GHQ.…”
Section: Discussionsupporting
confidence: 71%
“…In this sense, the correlation between the ERIQ effort scale and the DECORE-21 Cognitive Demands scale indicates that they both measure similar factors. Likewise, the effort factor is closely related to the emotional exhaustion dimension of MBI-HSS, and this makes sense, since excessive demands have a positive association with exhaustion [39]. The present study has also found a high and significant positive correlation between the ERIQ Effort scale and both the Anxiety and Insomnia scales and the total score of the GHQ.…”
Section: Discussionsupporting
confidence: 71%
“…These emotional demands cause emotional exhaustion. If such exhaustion prolongs for a passage of time, then it creates an intention among employees to leave their workplace (Azharudeen & Arulrajah, 2018). This pressure is increased when an employee faces some pressure that affects their cognition.…”
Section: Burnout As a Mediator Between Job Demand And Work Engagementmentioning
confidence: 99%
“…Emotional exhaustion negatively affects the organizations and employee performance where employees have possible depressive disorder, approximately 46% and emotionally exhausted nearly 41% in the Covid 19 pandemic situation (Luceño-Moreno et al, 2020). Even in the Sri Lankan context, researcher explored the impact on emotional exhaustion (Azharudeen & Arulrajah, 2018;Jayarathna & Dharmadasa 2018;Thisera & Bandara, 2017;Thisera & Silva, 2017). Specifically, Azharudeen and Arulrajah (2018) found that 74% of Sri Lankan employees in the apparel industry are emotionally exhausted.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the Sri Lankan context, researcher explored the impact on emotional exhaustion (Azharudeen & Arulrajah, 2018;Jayarathna & Dharmadasa 2018;Thisera & Bandara, 2017;Thisera & Silva, 2017). Specifically, Azharudeen and Arulrajah (2018) found that 74% of Sri Lankan employees in the apparel industry are emotionally exhausted. Hence, it is evident that emotional exhaustion is a prevalent problem in the Sri Lankan context.…”
Section: Introductionmentioning
confidence: 99%